Health Promotion: Home Core and Flexibility Exercises to Manage Low Back Pain in Pregnancy - Saifudin Zuhri; Marti Rustanti; Sri Suwarni (Poltekkes Kemenkes Surakarta, 2025)
Background: Low back pain is a common complaint among pregnant women and is related to biomechanical adaptations, weight gain, and hormonal changes during pregnancy. Health promotion efforts, such as structured home exercise programs that focus on core stability and flexibility, can help alleviate these symptoms. The aim of this study was to evaluate the effectiveness of a structured home exercise program in preventing and managing low back pain in pregnant women in the second and third trimesters. Methods: A pre-experimental design with a single group and pretest-posttest approach was utilized, involving 42 pregnant women chosen through purposive sampling. The participants engaged in a Structured Home-Based Core Stabilization and Flexibility Exercise Program twice a week, with each session lasting 30–45 minutes over a span of eight weeks. Pain intensity was measured using the Visual Analog Scale (VAS). Due to the non-normal distribution of the pre- and post-intervention scores, the Wilcoxon Signed Rank Test was used for analysis. Results: The VAS score significantly decreased from 4.81 ± 1.44 to 1.93 ± 0.84 (p < 0.001), with an average reduction of 2.88 points. The effect size was very large (r = 0.87; 95% CI: 0.86–0.88), indicating a strong intervention effect on pain reduction. Conclusion: These findings indicate that the program is an effective non-pharmacological health promotion strategy and can be recommended for routine implementation in maternal health services to prevent and manage low back pain during pregnancy.